The Political Teachings of Jesus - Lindberg, Tod. (New York : HC/HarperCollins, 2007)
Since the beginning of the Christian era, people have used the words and ideas of Jesus to justify all manner of political action. Despite these repeated attempts, few have been able to move past the rhetoric and understand the true nature of Jesus's political views. Here, political analyst and commentator Lindberg goes beyond punditry to address how Jesus's words and teachings--once a radical set of ideas--have come to define our concept of government and our vision for society. Lindberg draws a crucial distinction between Christ's religious and his political teachings, presenting a detailed discussion of the world transformation that Jesus sought. Through close reading of the Sermon on the Mount and Jesus's parables, Lindberg offers a sophisticated portrait of Jesus as a teacher of unique insight and perception, one whose political views have transcended time and become essential to the way everyone lives in our society.--From publisher description.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Political and social views; Jesus Christ -- Teachings; Bible. -- Criticism, interpretation, etc